An Analysis of State-Level Policies and Opioid Overdose Deaths. (July 2020) - Adams, Nicole; Gundlach, Ellen; Cheng, Ching-Wei
Many legislative and regulatory changes have occurred at the state level in response to the opioid crisis in an attempt to decrease overdose deaths. We conducted a negative binomial, regression-based, interrupted time series analysis to evaluate the effects of policies on opioid overdose death counts for 2008–2017 in five Midwestern states: Illinois, Indiana, Kentucky, Michigan, and Ohio. Except for the Good Samaritan laws in Illinois, no single policy change was statistically significant in decreasing overdose deaths. Governmental involvement as a whole was significantly associated with an increase in overdose deaths in Indiana. Policies created to address opioid overdose mortality have had minimal impact in these five Midwestern states. Most of the legislation and regulation that have been created lack educational components for prescribers and community members, which may explain why these policies have not had the intended effect.